Gravity-assisted drainage imaging in the assessment of pediatric hydronephrosis - Acker, Matthew R.; Clark, Roderick; Anderson, Peter (Canadian Urological Association Journal, 2016)
Introduction: As early detection of hydronephrosis increases, we require better methods of distinguishing between pediatric patients who require pyeloplasty vs. those with transient obstruction. Gravity-assisted drainage (GAD) as part of a standardized diuretic renography protocol has been suggested as a simple and safe method to differentiate patients. Methods: Renal scans of 89 subjects with 121 hydronephrotic renal units between January 2004 and March 2007 were identified and analyzed. Results: Of all renal units, 65% showed obstruction. GAD maneuver resulted in significant residual tracer drainage in eight renal units, moderate drainage in 12 renal units, and some improvement in 40 units after the GAD maneuver. Of the eight renal units with significant residual tracer drainage, only two proceeded to pyeloplasty. After pyeloplasty, nine children had improved time to half maximum (T1/2 Max) and 13 were unchanged. Conclusions: Our study was limited due to its retrospective design and descriptive analyses, but includes a sufficient number of subjects to conclude that GAD as part of a diuretic renography protocol is an effective and simple technique that can help prevent unnecessary surgical procedures in pediatric patients.